The Relationship Between Health Literacy and Health Status Among Elderly People in Kerman - Mohabat Mohseni; Narges Khanjani; Abedin Iranpour; Raheleh Tabe; Vahid Reza Borhaninejad (Sālmand, 2015)
Objectives Elderly people are at risk of low health literacy outcomes and exposed to many health problems due to lack of personal independence. We aimed to investigate the relationship between health literacy and health status of older adults in Kerman, Iran. Methods & Materials This was a cross-sectional study in which 200 elderly people were questioned in Kerman. Health literacy was measured using the Test of Functional Health Literacy in Adults (TOFHLA) And health status was measured using the Activity Daily Living tool and 10 questions of the short form of SF-36. To analyze the data we used descriptive statistics and to study the relationship among variables, statistical tests such as Chi-square, T, and one-way ANOVA were used. Results Most of the elderly people had inadequate health literacy (52.5%). There was a statistically significant association between health literacy and education (P=0.021) as well as occupation (P=0.041) in the elderly. We also found a statistically significant association between ADL and health literacy (P=0.038), but there was no statistically significant association between age, sex, marital status, economical status, and physical functional with health literacy. Conclusion Enhancing health literacy may be an effective strategy to improve elderly people’s health status. According to the results of this study, education and health-promoting behavior as well as improving health literacy are recommended in planning health promotion programs